The Role of Natural Language Processing in Requirement Engineering - Ahmed, Hussin; Hussain, Azham; Baharom, Fauziah (International Journal of Engineering and Technology, 2018)
The major objective of Software Requirements Specification (SRS) is providing sufficient information for software developers to build software product successfully. However, the current features of natural language hinders processing and analysis of requirements due to its ambiguous nature. Over the years, many Natural Language Processing (NLP) approaches were emerged to tackle this problem to detect errors or extract useful information from requirements documents. In this paper, a review of these approaches has been represented to reveal the role of NLP in requirement engineering and depict the current dilemma of SRS processing.Â Â